Pressure bag irrigation vs manual pressure and gravity drainage for reducing patient discomfort during flexible cystoscopy, A Study protocol for a randomised double blinded controlled trial - David Armany; Ankur Dhar; Ashan Canagasingham; Lawrence H. C. Kim; Audrey Wang (BMC Urology)
Abstract Background Flexible cystoscopy is widely used for the diagnosis and surveillance of various urological conditions and is commonly performed in an outpatient setting under local anaesthesia. Various adjuncts have been proposed to reduce patient discomfort, with the most notable being the manual bag squeeze method. This approach elevates irrigation fluid pressure, induces hydrodistension, and has received a strong recommendation from the European Association of Urology (EAU). However, the manual bag squeeze method is limited by inconsistencies in the pressure applied by individuals and the need for additional staff members to perform the procedure. This trial aims to assess the efficacy of standardised pressure bags in elevating irrigation fluid pressure during flexible cystoscopy and its impact on reducing mean pain scores, compared to conventional gravity drainage and the manual bag squeeze manoeuvre. Methods A randomised, controlled, double blinded, single-centre, parallel-group trial will be conducted. Participants scheduled to undergo flexible cystoscopy will be recruited, screened for eligibility and randomised to one of three study groups: (1) Intervention 1 – Pressure bag Group, (2) Intervention 2 – Manual bag squeeze group, and (3) Control – Gravity drainage group with a simulated bag squeeze. Randomisation will be stratified based on participants’ history of prior flexible cystoscopy. The primary outcome is the mean pains score reported by participants immediately after the procedure, assessed using a Numerical Rating Scale (NRS). Secondary outcomes include Patient Reported Outcome Measures (PROMIS) surveys at day 7 post flexible cystoscopy to evaluate for pain intensity (1a), Pain inference (short form 6a) and emotional distress-anxiety (Short form 4a), as well as the incidence of complications reported at day 30 post-procedure. Discussion This trial will evaluate the role of pressure bags to elevated fluid irrigation pressure and its effect on reducing patient discomfort during flexible cystoscopy using a rigorous methodology. If proven to be effective, pressure bag fluid irrigation has the potential to be implemented as one of the standards of practice for flexible cystoscopies. Trial registration Australian New Zealand Clinical Trials Registry (ANZCTR). Prospective Registration Number: ACTRN12623000799651. Date of Registration 26/07/2023.